УМЫКАНИЕ ДЕВУШКИ В КАРАКАЛПАКСКОМ ФОЛЬКЛОРЕ - Бекжанова, Б. (SCIENCE and SOCIETY, 2017)
The article is devoted to the study of the facts of marriage by means of stealing the bride in the Karakalpak folklore works (tales, eposes, etc.). The author researches the historical and social backgrounds of stealing the future bride and their variants in Karakalpak folklore, the peculiarities of this type of marriage on the material of folklore.
Keywords: Karakalpak folklore; ethnography; customs and rituals; marriage by abduction form